Shi’ite Ideology Bias in Al-Qummi Tafsir: Study of Ali Imran and Al-Nisa’ Chapters - Ahmad Zainal Abidin (UIN Sunan Kalijaga Yogyakarta, 2018)
The study of political bias in Quranic commentary is of great interest following the contexts that led to its emergence. The verse of the Qur'an is often used as a legitimation of understanding in religious discourse. The study of al-Qummi's commentary explains how the verses of the Qur'an are understood in such a way by a person living in the certain context to favor the Shi'a school and attack its opponents. It also explains how the interpretation becomes a field of meaning contestation. This tendencies were found in al-Qummi commentary on Alu Imran and al-Nisa’ Surahs. The presence of such a biased interpretation can not be separated from the author's cultural and social political context as he lives in the midst of contests, rivalries and political intrigues of Muslim groups in a particular era in history.[Kajian tentang bias politik dalam tafsir Al-Quran sangat menarik dilakukan terkait konteks yang menyebabkan kemunculannya. Ayat Al-Qur'an sering digunakan sebagai legitimasi pemahaman dalam wacana agama. Dengan menggunakan pendekatan historis dan komparatif, studi terhadap tafsir al-Qummi ini menemukan bagaimana ayat-ayat Al Qur'an dipahami sedemikian rupa oleh seseorang yang hidup dalam konteks tertentu untuk mendukung madzhab Syiah dan menyerang lawan-lawan politik. Penafsiran yang demikian berbeda dengan Al-Qur ’an dan Tafsirnya karya dari Tim Kementerian Agama. Studi juga menemukan bagaimana tafsir al-Quran menjadi medan kontestasi makna antar kelompok. Kecenderungan ini ditemukan dalam penafsiran al-Qummi tentang surah Ali Imran dan al-Nisa’. Kemunculan interpretasi yang bias seperti itu tidak dapat dipisahkan dari konteks budaya dan sosial politik al-Qummi ketika ia hidup di tengah-tengah persaingan dan intrik politik antara kelompok Muslim di era tertentu dalam sejarah Islam.]